Worldwide trends in body-mass index, underweight, overweight, and obesity from 1975 to 2016: a pooled analysis of 2416 population-based measurement studies in 128·9 million children, adolescents, and adults - Abarca-Gómez, Leandra; Abdeen, Ziad A; Hamid, Zargar Abdul; Abu-Rmeileh, Niveen M; Acosta-Cazares, Benjamin; Acuin, Cecilia; Adams, Robert J; Aekplakorn, Wichai; Afsana, Kaosar; Aguilar-Salinas, Carlos A; Agyemang, Charles; Ahmadvand, Alireza; et al. (Elsevier, 2017)
Acuin, Cecilia (IRRI author)